Potential Antioxidant Effect of Fruit Peels for Human Use from Northern Peru, Compared by 5 Different Methods [Potencial Efecto Antioxidante de Las Cáscaras de Frutas Para Uso Humano del Norte de Perú, Comparado por 5 Métodos Diferentes] - Martinez-Salinas, J; Rios-Ramirez, M (MS-Editions, 2021)
The objective of the work was to determine the antioxidant potential in vitro of freeze-dried peel extracts of 20 fruits from the northern region of Peru through five tests (Folin-Ciocalteu, DPPH., ABTS+., FRAP and CUPRAC). According to multivariate statistical analyzes, five groups were found: (i.) peel extracts with the highest values of antioxidant capacity (AC) from custard apple, and star fruit; (ii.) rind extracts with high AC values from quince, sweet granadilla, guava, and black grape; (iii.) husk extracts with middle values of AC from passion fruit, and red mombin; (iv.) shell extracts with low AC values from tangerine, mandarine, and bitter orange; and, (v.) coating extracts with the lowest AC values from pawpaw, red pawpaw, muskmelon, dragon fruit, yellow and red indian figs, pear, apple, and green grape. To conclude, the fruit lyophilized-husk extracts of custard apple, star fruit, quince, sweet granadilla, guava, and black grape obtained the best AC. © 2021, MS-Editions. All rights reserved.